1998
DOI: 10.1016/s0014-5793(98)01589-0
|View full text |Cite
|
Sign up to set email alerts
|

Purification and partial characterization of a ‘short' insectotoxin‐like peptide from the venom of the scorpion Parabuthus schlechteri

Abstract: A disulfide-rich, low-molecular-mass toxin-like peptide has been isolated from Parabuthus schlechteri venom using gel filtration, ion exchange, and reversed phase chromatography. Partial characterization of this peptide reveals a relationship with four-disulfide bridge proteins belonging to the family of short' insectotoxins (44% residue identity). In recognition hereof, the peptide was named PBITx1 (sITx10). Our work also reports on the deduced sequences of two other`short' insectotoxins from Buthus eupeus, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Recent studies have identified many low-molecular-mass peptide toxins from Lqh and other scorpion venoms. Sequence comparisons have determined that Lqh-8/6 from L. quinquestriatus hebraeus (2), Bs8 and Bs14 from Buthus sindicus (4), and PBITx1 from Parabuthus schlechteri (53) are similar to ClTx from Lqq venom. Therefore, there is a possibility that this Lqh toxin will be one previously identified; alternatively, this study will result in the identification of a novel peptide toxin that selectively inhibits CFTR.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified many low-molecular-mass peptide toxins from Lqh and other scorpion venoms. Sequence comparisons have determined that Lqh-8/6 from L. quinquestriatus hebraeus (2), Bs8 and Bs14 from Buthus sindicus (4), and PBITx1 from Parabuthus schlechteri (53) are similar to ClTx from Lqq venom. Therefore, there is a possibility that this Lqh toxin will be one previously identified; alternatively, this study will result in the identification of a novel peptide toxin that selectively inhibits CFTR.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies indicated that native PBTx1 blocks Shaker-type Kv1.1 channels expressed in Xenopus laevis oocytes with a K d value of ϳ150 nM (34). A more in-depth analysis has revealed the presence of a more potent contaminating peptide in this sample, PBTx3, recently characterized by our group (30).…”
Section: Physiological Effects Of the New Subfamily ␣-Ktx11mentioning
confidence: 85%
“…Five residues recognized as "critical residues" in Kv-blocking activity (11) in ChTx, Lys 27 , Met 29 , Asn 30 , Arg 34 , and Tyr 36 , are well conserved among different ␣-KTx peptides. However, none of them is conserved in PBTx1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study was undertaken to find compounds or toxins in the venom of P. transvaalicus that modulate physiological processes at the cellular level; this was done for the following reasons: (a) very little is known about the bioactive substances present in the venom of this scorpion [7,8]; (b) the discovery of new toxins can be the key to gain insight into the molecular mechanisms of scorpionism; (c) selective toxins can be used for purifying channels from native tissue, determining their subunit composition [9] and for elucidating the pharmacology and physiological roles of voltagedependent Na + , Ca 2+ and K + channels [10][11][12] in target tissues. Voltage-dependent K + channels in particular serve important functions in many signal-transduction pathways in the nervous system: they are involved in neuron excitability; they influence the resting membrane potential, the waveforms and frequencies of action potentials; and they determine the thresholds of excitation [13].…”
mentioning
confidence: 99%